Beans (Phaseolus vulgaris L.) - Mkandawire, A.B.C. (National Bean Programme, 1990)
Aspects of a bean project proposal in Malawi are discussed as follows: objectives, review of bean research and production, government strategies, assistance from international institutions, institutional framework for bean industry, project justification (seed multiplication and distribution; cropping systems; on-farm research; drought/heat tolerance; pathological, entomological, and breeding research), project strategy and implementation, expected development impact, and estimated budget. (CIAT)